A systematic review and qualitative synthesis of adolescents' views of sexual readiness. (1st December 2016) - Templeton, Michelle; Lohan, Maria; Kelly, Carmel; Lundy, Laura
Abstract: Aim: The aim of this study was to synthesize the qualitative evidence investigating adolescents' views on heterosexual readiness. Background: Adolescents' understandings of sexual readiness are often missing in research and debates on sexual health and related concepts like sexual consent. Research to date has predominantly focussed on age and socio‐cultural predictors of sexual debut, thus failing to explain how adolescents themselves conceptualize their readiness for heterosexual relations. Design: A systematic review and thematic synthesis of qualitative evidence. Data sources: CINAHL, Psychinfo, PubMed, Web of science were searched, 1985–Feb 2016. Review methods: Critical Appraisal Skills Programme checklist was used to assess methodological quality. A thematic synthesis focused on commonalities and variations in the data from included studies on adolescents' perspectives of their readiness for sex. Results: Sixteen studies were included. Themes identified were: social learning, relationships and implications for sexual health promotion and practice. Conclusions: Adolescents may not view initiating sex as problematic, focusing instead on the rewards sex brings and less on health concerns. Adolescents tend to reproduce dominant gender norms of masculinity and femininity in communication about sexual decision‐making, which are sometimes influenced by social scripts of career aspirations and ethnic identity. Age was also significant in adolescents' accounts. Early adolescence is a critical period when understandings of gender equality become embedded, thus an opportunity to engage adolescents in critiquing ideas about gender equality and sexual rights. Further research exploring adolescents' understandings of sexual readiness is required. We recommend a participatory approach to support the inclusion of adolescent voices to inform contextually relevant sexual health promotion strategies.